Răspuns :
(x-1)/3 - (1+2x)/2 = 5/6
2(x-1)-3(1+2x)=5
2x-2-3-6x=5
-4x-5=5
-4x=5+5
-4x=10
x=-10/4
x=-5/2
x=-2,5
2(x-1)-3(1+2x)=5
2x-2-3-6x=5
-4x-5=5
-4x=5+5
-4x=10
x=-10/4
x=-5/2
x=-2,5
Salut,
Dacă înmulțești cu 6 fiecare termen al ecuației, atunci obții:
2(x -- 1) -- 3(2x + 1) = 5, sau 2x -- 2 -- 6x -- 3 = 5, sau --4x = 10, deci x = --5/2.
Green eyes.
Dacă înmulțești cu 6 fiecare termen al ecuației, atunci obții:
2(x -- 1) -- 3(2x + 1) = 5, sau 2x -- 2 -- 6x -- 3 = 5, sau --4x = 10, deci x = --5/2.
Green eyes.